Retraite du milieu agricole : enjeux individuels, familiaux et sociaux - Lyson Marcoux; Maxime Hébert (Enfances, Familles, Générations, 2020)
Research Framework: Quebec agriculture is still characterized by family farms that are usually transferred from generation to generation. Considering that the Quebec agricultural lifestyle generally interweaves the “individual”, “family” and “entrepreneurial” spheres, that many farmers are expected to sell their business in the next few years and that this transition raises many questions and challenges, factors influencing adaptation to this new reality deserve to be studied. Objectives: The purpose of this study is to better understand farmers’ current experiences with the transfer or sale of their business to their children or a third party from a psychological angle linked to the systemic approach. Methodology: Nine semi-structured interviews were conducted with farmers (6 men and 3 women, mean 59 years-old), who have withdrawn from their company (between 1 month and 10 years). Results: This study sheds light on the issues and challenges inherent to the agricultural community during the working life and after the transfer or sale of the business. Resilience is evident in all participants. They usually remain professionally active, which is inconsistent with traditional retirement models. Conclusions: Considering that the majority of retirees in the sample continue to get involved during and after the transfer of their business, the reasons that motivate them as well as the psychological and family issues that arise from this deserve to be deepened. Contribution: This study draws a psychological portrait of this transition in Quebec (Canada). Considering the importance reported by the participants to remain active and socially engaged, social innovations are suggested in order to promote the adaptation to retirement of farmers who cannot continue to work in the field.